DFT Study on the Molecular Mechanism, Thermodynamic and Kinetic Parameters of Cycloaddition Reaction of Aziridine with CO2 in the Presence of Organocatalysts (TBD and 7-Azaindole) - Gebre, Tesfaye Tadesse; Lilisho, Teshome Abute; Gosa, Birhanu Bekele (Trends in Sciences, 2022)
The catalytic conversions of CO2 into value added chemicals have attracted the interest of many visionary researchers. In this work, the coupling reaction of aziridine with CO2 has been investigated in the absence and presence of organocatalysts (TBD and 7-azaindole) computationally using density functional theory method. The kinetic and thermodynamic parameters of each mechanism were calculated at B3LYP/6-31G (d) level. The results show that, the TBD and 7-azaindole catalyzed reactions of aziridine with CO2 have significantly lower the energy barrier compared to a single step concerted non-catalyzed one. In TBD catalyzed reaction, mechanism I in which the TBD catalyst first interact with CO2 to form TBD-CO2 adduct (zwitterion) and then the zwitterion formed facilitated the ring opening of aziridine to form intermediate is the favorable path. In the case of 7-azaindole catalyzed reaction, mechanism 1 is the most favorable pathway in both gas phase and water phase. However, these parameters were significantly affected in the presence of water using Solvent Model Density (SMD).